2015
DOI: 10.1165/rcmb.2014-0024oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pneumococcal Autolysin for KLF4 Expression and Chemokine Secretion in Lung Epithelium

Abstract: In severe pneumococcal pneumonia, the delicate balance between a robust inflammatory response necessary to kill bacteria and the loss of organ function determines the outcome of disease. In this study, we tested the hypothesis that Krueppel-like factor (KLF) 4 may counter-regulate Streptococcus pneumoniae-related human lung epithelial cell activation using the potent proinflammatory chemokine IL-8 as a model molecule. Pneumococci induced KLF4 expression in human lung, in primary human bronchial epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 44 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…Notably, the lung-derived adenocarcinoma A549 cell line and the virus-transformed BEAS-2B bronchial cell line have been used for studying the function of virulence factors and the alterations that take place in the bacterium and the host cell upon bacteria-host interactions (3,6568). However, the suitability of these cell lines as in vitro models for investigating the interaction between S. pneumoniae and nasal or lung mucosal cells has not been verified directly.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the lung-derived adenocarcinoma A549 cell line and the virus-transformed BEAS-2B bronchial cell line have been used for studying the function of virulence factors and the alterations that take place in the bacterium and the host cell upon bacteria-host interactions (3,6568). However, the suitability of these cell lines as in vitro models for investigating the interaction between S. pneumoniae and nasal or lung mucosal cells has not been verified directly.…”
Section: Discussionmentioning
confidence: 99%
“…Zahlten et al and Herta et al have previously shown that LytA (autolysin) dependent release of bacterial DNA was a controlling factor in the induction of KLF4 in epithelial cells and macrophages during S. pneumoniae infection 167,169 . The present experiment was done to see whether the induction of KLF4 was also dependent on autolysin like in the other cell types.…”
Section: Pneumococci-induced Expression Of Klf4 Depends On Autolysismentioning
confidence: 99%
“…KLF4 has been documented to have a role in the establishment of the skin barrier. Given that it helps in the development of skin barrier, KLF4 KO mice die shortly after birth due to spontaneous loss of body fluids 156 136,167 (see below, 3.7).…”
Section: Functional Role Of Klf4mentioning
confidence: 99%
See 1 more Smart Citation
“…LytA is the major autolysin of pneumococci (Lopez and Garcia 2004) and causes the release of intrabacterial components such as PLYand bacterial DNA. Since the pneumococci-related expression of the immunomodulatory transcription factor Krueppellike factor (KLF) 4 (McConnell and Yang 2010) in human lungs seems also to depend on LytA-related pneumococcal autolysis (Zahlten et al 2015b) and as KLFs have an impact on lung cell activation in pneumococcal infection (Zahlten et al 2010(Zahlten et al , 2013(Zahlten et al , 2015a, further investigation of LytA-related activation of lung tissue is highly recommended.…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%